PRODUCTION OF THE PROFILED NICKEL CATHODE FALLOUT MICRO-ALLOYED BY SULFUR - L. V. Rybinskaja; A. N. Zadiranov; V. A. Brukvin (Литьë и металлургия)
The high efficiency of application of electrolytes of new generation on the basis of methane-sulfonic acid and nickel acetate at production of profiled cathode sediments is shown.